The Pore Structure of Marine to Continental Transitional Shales in the Permian Shanxi Formation on the East Margin of the Ordos Basin, China. (22nd August 2022) - Wang, Tao; Tian, Fenghua; Deng, Ze; Hu, Haiyan; Xie, Zhitao
Abstract : The pore structure is an important factor in determining the storage capacity for shale gas development. Twelve samples were selected from the marine to continental transitional shales in the Shanxi Formations on the eastern margin of the Ordos Basin, and their nanoscale pore structure was investigated by a variety of low-temperature N2 adsorption (LT-N2 GA) and low-pressure CO2 adsorption (LP-CO2 GA) and high-pressure mercury intrusion (HPMI) experiments. The shale pores are complex and are mainly mesopores, which range mainly from 10 nm to 40 nm and greatly contribute to the pore volume (PV), whereas pores with a diameter less than 0.8 nm greatly contribute to the specific surface area (SSA) of the shale. The pore structure is affected by the TOC content, organic matter maturity, and illite/smectite (I/S) mixed layer content. The total PV increases with the increase in TOC content, organic matter maturity, and I/S mixed layer content. The effects of pores on the occurrence shale gas were determined by high-pressure methane adsorption experiments. The maximum adsorption amount of methane was positively correlated with the SSA of the micropores, indicating that the micropores have a large SSA, which controlled the adsorbed gas content of the shale. The mesopores provide the majority of the PV, which mainly corresponds to the volume of free gas in the shale, and the macropores are mainly micron-sized pores, which can form the main migration channels for shale gas.